Océan Indien et Océan Austral - Iles Éparses / Service hydrographique de la marine . 1934 - France. Service hydrographique de la marine; (1963)
Mars 1963 édition no. 2 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Ile St. Paul (scale 1:20,000) -- Ile Amsterdam (scale 1:70,000) -- Iles Heard et Mac Donald (scale 1:372,300).; Includes 6 coastal profiles Grayscale;